ANTHROPOLOGICAL CATASTROPHE OF THE GLOBALIZED WORLD: EDUCATIONAL ASPECT - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The problems of education and man’s existence in the background of complex global transformational processes of the Information age are dealt with in the article. The article discusses the impact of images of future on selecting the vector of educational reforms. The ambiguous influence on man and nature of the further technocratic way of civilization development aimed at accumulating scientific knowledge excluding the spiritual experience of the mankind is analyzed. It is emphasized that the race for external indicators of educational achievement, by copying others’ educational experience without taking into account the peculiarities of the mentality of the Ukrainian people, their philosophical and historical heritage, leads to the destruction of Ukraine as a unique European state.